Quantitative profiling of cytokines and chemokines in DOCK8‐deficient and atopic dermatitis patients. Issue 2 (15th October 2018) - Jacob, Minnie; Bin Khalaf, Duaa; Alhissi, Safa; Arnout, Rand; Alsaud, Bander; Al‐Mousa, Hamoud; Lopata, Andreas L.; Alazami, Anas M.; Dasouki, Majed; Abdel Rahman, Anas M.
Abstract: Background: Hyper‐IgE syndromes (HIES) are a clinically overlapping, heterogeneous group of inborn errors of immunity characterized by elevated serum IgE level, eosinophilia, atopy, and immune dysregulation. Deficiency of DOCK8 protein is potentially a life‐threatening autosomal recessive HIES and only curable with bone marrow transplantation. Hence, the diagnosis of DOCK8 deficiency is critical and should be sought at an early stage to initiate definitive therapy. Methods: Serum samples from patients with DOCK8 deficiency and atopic dermatitis were profiled on a cytokine/chemokine panel for potential differential expression. Results: CXCL10 and TNF‐A were upregulated in DOCK8 patients when compared to AD, possibly contributing toward increased susceptibility to infections and cancer. In contrast, epidermal growth factor (EGF) was significantly downregulated in a subgroup of DOCK8‐deficient and AD patients, while IL‐31 expression was comparable between both DOCK8‐deficient and AD cohorts, possibly contributing toward pruritus seen in both groups. Conclusion: This comprehensive cytokine profile in HIES patients reveals distinctive biomarkers that differentiate between the DOCK8‐deficient and AD patients. The unique expression profile of various inflammatory cytokines in patients with DOCK8 deficiency vs atopic dermatitis likely reflects disease‐specific perturbations in multiple cellular processes and pathways leading to a predisposition to infections and allergies seen in these patients. These data agree with the role for EGF replacement therapy in EGF‐deficient individuals with AD as well as DOCK8 deficiency through a potential shared pathway. In addition, these novel biomarkers may be potentially useful in distinguishing DOCK8 deficiency from AD allowing early‐targeted treatment options.